MODEL PEMBELAJARAN MEMBACA AL-QUR’AN PADA ANAK DISABILITAS DI SLB SANTI RAMA JAKARTA SELATAN - Alma’zumi, Adib; Shunhaji, Akhmad; Sarnoto, Ahmad Zain (Profesi : Jurnal Ilmu Pendidikan dan Keguruan, 2023)
This research examines Learning Model for Reading the Qur'an in Children with Deaf Disabilities at SLB Santi Rama, South Jakarta. This study proves that the learning model for children with hearing disabilities at SLB Santi Rama, South Jakarta uses the Iqro' method. The main problem to be studied and answered through this research is how is the learning model for reading the Koran for children with hearing disabilities at SLB Santi Rama, South Jakarta.The interesting thing found in this research is that learning the Koran for SLB Santi Rama students in South Jakarta is that children with hearing disabilities are able to speak and read the Koran, while they do not hear what they say themselves. And communication with facial expressions. This research method is descriptive qualitative which concentrates on learning models and methods. The main source is “principal. Vice principals, teachers, guardians of students, students, secondary sources used are books, journals, articles, papers and writings in print and electronic media related to the research. Data collection techniques with interviews, observation and documentation. After all the data collected is processed and analyzed, especially in the management of learning for children with hearing disabilities at SLB Santi Rama, South Jakarta using the Iqro' method